Subacute thyroiditis and rapidly developing goiter in a 16-year-old female: a case report - Marcos Estrada; Meriam Avades; María Parra; Patricia Altagracia; Carmen Lazala (Instituto Tecnológico de Santo Domingo (INTEC), 2023)
Subacute thyroiditis (SAT) is an inflammatory disease of the thyroid gland with multiple etiologies and clinical features, often challenging to recognize. The classic presentation is the painful, granulomatous thyroiditis (DeQuervain's) characterized by diffuse swelling of the gland, usually preceded by an upper respiratory tract infection. A painless variant, also referred to as autoimmune subacute thyroiditis, has been documented and is strongly linked to postpartum state, reported following ~10% of pregnancies. It can be differentiated from the former by the presence of anti-thyroid antibodies, which classifies it as an autoimmune thyroiditis. Any spontaneous development of painful swelling of the thyroid gland warrants a complete work up that includes thyroid hormones, thyroid autoimmune panel, acute phase reactant titers, and, if available, imaging that may lead to the diagnosis of an inflammatory or infectious cause of thyroiditis.